Analysis of Exchange Rate Fluctuations on Airfares and Domestic Flight Demand in Indonesia - Yudha Pratidhina Ayu Maghfirany; Bakhtiar Efendi; Annisa Ilmi Faried (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
This study analyzes the impact of exchange rate fluctuations on airline ticket prices and domestic air travel demand in Indonesia within a simultaneous equation model framework that integrates macroeconomic and airline operational factors over the post-pandemic period of 2013–2024. A quantitative approach using the Two-Stage Least Squares (2SLS) method is employed to address the endogeneity between ticket prices (HTP) and passenger demand (PPD). The main variables include the rupiah exchange rate, aviation fuel prices, airline operational costs, and consumers’ purchasing power. Estimation results indicate that the model is overidentified and satisfies all classical assumptions, with normally distributed residuals (p-value 0,9659 and 0,9763), homoscedasticity (p-value 0,3399 and 0,1422), and an absence of autocorrelation (p-value 0,2226 and 0,2489). Simultaneously, flight demand and operating costs exert an effect on ticket prices, with very high explanatory power (R² 0,9982; Prob F 0,0000), while the exchange rate serves as a cost transmission channel through the exchange rate pass-through mechanism. On the demand, ticket prices, exchange rates, and purchasing power significantly affect the number of passengers (R²:0,9782 and Prob F 0,000001), confirming a bidirectional causal relationship between price and demand after addressing endogeneity. These findings suggest that Rupiah depreciation and rising operating costs drive up ticket prices, which potentially suppresses demand; however, this impact can be mitigated by strengthened purchasing power and domestic economic recovery. Consequently, macroeconomic stability remains a pivotal factor for the sustainability of Indonesia’s domestic aviation demand in the post-pandemic era.